Urea de liberación lenta en dietas para bovinos productores de carne: Digestibilidad, síntesis microbiana y cinética ruminal (2013)
There is an interest in finding alternatives for urea that can slowly degrade in the rumen to avoid problems and restrictions derived from its use. The objective of this study was to evaluate the effects of substituting conventional urea for slow release urea (SRU) in diets for beef cattle, on voluntary consumption, coefficients of apparent (ARD), intestinal (IRD) and total (TRD) rumen digestibility of nutrients, microbial protein synthesis, and rumen kinetics. Four Nelore steers (live weight 565±45 kg) were used, with a rumen cansnula, in a Latin Square experimental design of 4×4. The treatments were the following: 0 SRU(100 % urea, 33 SRU(66 % urea and 33 % SRU; 66 SRU(33 % urea and 66 % SRU and 100 SRU(100% SRU. The data were analyzed through ANOVA and when there were treatment effects (p=0.05), a polynomial regression analysis was performed. The dry matter consumption (DMC), the ARD, IRD and TRD of the DM, protein (PC) and non-fibrous carbohydrates (NFC) were not affected (p>0.05) by treatments. However, the rumen flow of DM, organic matter and PC was linearly reduced (p=0.05) when increasing the level of SRU in the diet. The inclusion of SRU increased linearly the ARD of neutral detergent fiber (NDF) (p=0.05). Substituting urea for SRU did not affect (p>0.05) microbial protein synthesis or rumen kinetics. We conclude that the use of SRU in the diet for Nelore steers improved the apparent rumen digestibility of fiber, without affecting microbial protein synthesis and rumen kinetics. © 2009 Bio-Rad Laboratories.